Trihydrazine Dihydriodide‐Assisted Fabrication of Efficient Formamidinium Tin Iodide Perovskite Solar Cells. Issue 9 (19th July 2019) - Li, Fengzhu; Fan, Haochen; Zhang, Jie; Huang, Jin-Hua; Wang, Pengcheng; Gao, Caiyan; Yang, Lian-Ming; Zhu, Zonglong; Jen, Alex K.-Y.; Song, Yanlin; Jiang, Ke-Jian
Abstract : The deposition of a uniform and dense tin‐based perovskite layer with low defect‐caused background carrier density is crucial for achieving efficient tin perovskite solar cells (PSCs). These defects are mainly caused by the rapid oxidation of Sn 2+ to Sn 4+ in tin perovskite during device fabrication. Herein, trihydrazine dihydriodide ((N2 H4 )3 (HI)2 ) is used as an additive for solution deposition of a formamidinium tin iodide (FASnI3 ) perovskite layer. The resultant FASnI3 layer is homogeneous with full surface coverage; moreover, the content of Sn 4+ is significantly reduced in the film from the SnI2 precursor owing to the reductive property of (N2 H4 )3 (HI)2 . With the high‐quality FASnI3 layer as a light absorber, planar‐heterojunction perovskite solar cells are fabricated, exhibiting a maximum power conversion efficiency of 8.48% and good reproducibility. This work opens new possibilities for achieving efficient lead‐free tin‐based perovskite solar cells. Abstract : Trihydrazine dihydriodide is successfully used as an additive for solution deposition of a formamidinium tin iodide (FASnI3 ) perovskite layer, resulting in improved surface morphology and reduced carrier concentration. Using the derived FASnI3 layer as a light absorber, a maximum power conversion efficiency of 8.48% is achieved in a planar‐heterojunction solar cell using common precursor SnI2 with 99% purity.